2019
DOI: 10.30630/joiv.3.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of TCP Vegas over TCP Reno and TCP NewReno over TCP Reno

Abstract: In the Transport layer, there are two types of Internet Protocol are worked, namely-Transmission Control Protocol (TCP) and User datagram protocol (UDP). TCP provides connection-oriented service and it can handle congestion control, flow control, and error detection whereas UDP does not provide any of service. TCP has several congestion control mechanisms such as TCP Reno, TCP Vegas, TCP New Reno, TCP Tahoe, etc. In this paper, we have focused on the behavior performance between TCP Reno and TCP Vegas, TCP New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
3
0
5
Order By: Relevance
“…Where TCP Vegas provided a fair service compared with Reno [11]. While in literature [12] authors focused on the efficiency of the actions between TCP Reno and TCP Vegas when they share the same router bottleneck. Where a drop tail and RED algorithm is used on the router and it has been found that the TCP Vegas does not have better droptail efficiency due to the difference in router buffer occupation.…”
Section: Introductionmentioning
confidence: 99%
“…Where TCP Vegas provided a fair service compared with Reno [11]. While in literature [12] authors focused on the efficiency of the actions between TCP Reno and TCP Vegas when they share the same router bottleneck. Where a drop tail and RED algorithm is used on the router and it has been found that the TCP Vegas does not have better droptail efficiency due to the difference in router buffer occupation.…”
Section: Introductionmentioning
confidence: 99%
“…Chowdhury et al [5] e Mohammad et al [7] apresentam um comparativo entre os desempenho do controle de congestionamento das principais versões do protocolo TCP.…”
Section: Trabalhos Relacionadosunclassified
“…A versão TCP Vegas apresenta uma abordagem preditiva, pois utiliza o tempo de ciclo de cada segmento como referencia para prever congestionamentos e antecipar-se a perda de pacotes. Quando o RTT indica uma tendência ao congestionamento, a quantidade de segmentos transmitidos e reduzida a fim de evitar a ocorrência da perda [5], [6].…”
Section: Introductionunclassified
“…We use the result of dividing the average RTT by the estimated network diameter to estimate the average link delay of AS2. Based on the performance detection information obtained from SDN gateways, the SDN controller can obtain the average link available bandwidth using bandwidth estimation algorithms, such as TCP Westwood (Haveliwala et al, 2020) and TCP Vegas (Chowdhury and Alam, 2019). This SDN gateway-based architecture can not only avoid the high cost of making subnets SDN-enable but also avoid the long convergence time collecting the complete network information.…”
Section: Control Plane Designmentioning
confidence: 99%